Defensive responses of gopher tortoises (Gopherus polyphemus) are influenced by risk assessment and level of habituation to humans - Bateman, Bill; Fleming, P.; Jones, B.; Rothermel, B. (Brill, 2014)
Species that are either sessile or too slow to resort to flight may instead rely on defences suchas natural armour or protective structures, but they will still face the same economic decisionsas do more mobile species about when to re-emerge from cover. The gopher tortoise (Gopheruspolyphemus) is a species of conservation significance due to its important role as an ecosystem engineer and habitat loss due to human activities. In this study, we examined escape responses ofgopher tortoises approached by a human observer. Our data supported our prediction that the levelof disturbance would influence escape responses, with animals that were picked and handled taking longer to emerge and move off than animals that had simply been approached or approached and walked around. We also found that tortoises took half as long to extend their heads at our studysite, where tortoises exposed to a high level of benign human activity over a long period, compared with an adjacent site where there had been minimal human interaction with tortoises. These data suggest that gopher tortoises adjust their escape responses according to the level of risk they are exposed to. Over the long-term, this plasticity in escape responses can potentially result in some level of habituation to human presence.